Intraperitoneal metastasis of ovarian cancer: new insights on resident macrophages in the peritoneal cavity - Miyamoto, Taito; Murphy, Brennah; Zhang, Nan (Frontiers in Immunology, 2023)
Ovarian cancer metastasis occurs primarily in the peritoneal cavity. Orchestration of cancer cells with various cell types, particularly macrophages, in the peritoneal cavity creates a metastasis-favorable environment. In the past decade, macrophage heterogeneities in different organs as well as their diverse roles in tumor settings have been an emerging field. This review highlights the unique microenvironment of the peritoneal cavity, consisting of the peritoneal fluid, peritoneum, and omentum, as well as their own resident macrophage populations. Contributions of resident macrophages in ovarian cancer metastasis are summarized; potential therapeutic strategies by targeting such cells are discussed. A better understanding of the immunological microenvironment in the peritoneal cavity will provide a stepping-stone to new strategies for developing macrophage-based therapies and is a key step toward the unattainable eradication of intraperitoneal metastasis of ovarian cancer.